Travel ban effects on SARS-CoV-2 transmission lineages in the UAE as inferred by genomic epidemiology. - Andreas Henschel; Samuel F Feng; Rifat A Hamoudi; Gihan Daw Elbait; Ernesto Damiani; Fathimathuz Waasia; Guan K Tay; Bassam H Mahboub; Maimunah Hemayet Uddin; Juan Acuna; Eman Alefishat; Rabih Halwani; et al. (PLoS ONE)
Global and local whole genome sequencing of SARS-CoV-2 enables the tracing of domestic and international transmissions. We sequenced Viral RNA from 37 sampled Covid-19 patients with RT-PCR-confirmed infections across the UAE and developed time-resolved phylogenies with 69 local and 3,894 global genome sequences. Furthermore, we investigated specific clades associated with the UAE cohort and, their global diversity, introduction events and inferred domestic and international virus transmissions between January and June 2020. The study comprehensively characterized the genomic aspects of the virus and its spread within the UAE and identified that the prevalence shift of the D614G mutation was due to the later introductions of the G-variant associated with international travel, rather than higher local transmissibility. For clades spanning different emirates, the most recent common ancestors pre-date domestic travel bans. In conclusion, we observe a steep and sustained decline of international transmissions immediately following the introduction of international travel restrictions.